The brightening of Saturn's F ring - French, Robert S.; Showalter, Mark R.; Sfair, Rafael [UNESP]; Argueelles, Carlos A.; Pajuelo, Myriam; Becerra, Patricio; Hedman, Matthew M.; Nicholson, Philip D. (Academic Press Inc. Elsevier B.V., 2012)
Image photometry reveals that the F ring is approximately twice as bright during the Cassini tour as it was during the Voyager flybys of 1980 and 1981. It is also three times as wide and has a higher integrated optical depth. We have performed photometric measurements of more than 4800 images of Saturn's F ring taken over a 5-year period with Cassini's Narrow Angle Camera. We show that the ring is not optically thin in many observing geometries and apply a photometric model based on single-scattering in the presence of shadowing and obscuration, deriving a mean effective optical depth tau approximate to 0.033. Stellar occultation data from Voyager PPS and Cassini VIMS validate both the optical depth and the width measurements. In contrast to this decades-scale change, the baseline properties of the F ring have not changed significantly from 2004 to 2009. However, we have investigated one major, bright feature that appeared in the ring in late 2006. This transient feature increased the ring's overall mean brightness by 84% and decayed with a half-life of 91 days. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Saturn, Rings; Planetary rings; Photometry